KURIKULUM PENDIDIKAN AGAMA ISLAM BERBASIS LINGKUNGAN SEBAGAI PENGUATAN PENDIDIKAN HUMANISTIK DI SEKOLAH ADIWIYATA - Atiqoh, Layly; Saputro, Budiyono (Program Studi Pendidikan Agama Islam, 2017)
ISLAMIC EDUCATION CURRICULUM BASED ON ENVIRONMENT AS A REINFORCEMENT FOR HUMANISTIC EDUCATION IN ADIWIYATA SCHOOL. The main objectives of this study are to describe planning, development, implementation, a success and special quality of Islamic education environment based curriculum on Adiwiyata school SMPN 6 & SMPN 7 Salatiga. The research method is qualitative research. This research was conducted at Adiwiyata school SMPN 6 & SMPN 7 Salatiga. The main subjects of this study are the headmaster, the school committee, the vice principal, areas of curriculum, Head of Adiwiyata, teachers, and students. The technique of collecting data is by observating, interviewing, and documenting. The results of this study are the school has been: (1) planning the Islamic education environment based curriculum by conducting mapping of basic competencies to be an indicator, (2) carried out the development of the Islamic education environment based curriculum is integrated to the material and the environment, (3) implemented the Islamic education environment based curriculum by creating an annual planning, communicating to other stakeholders and teachers design the implementation of learning and assessment, (4) the special quality of the students is that they care about the environment around as a strengthening of humanistic education.